Phase Current Equalization Method of IPMSM-Based on-Board Boost Converter for Electric Vehicles - Yunkyung Hwang; Jaehong Kim; Minhyeok Lee; Juwon Choi; Kwanghee Nam (IEEE Access, 2025)
As the distance traveled per charge increases, the adoption of 800V batteries is increasing. However, most electric vehicle (EV) charging stations are designed to charge 400V batteries. However, if the installed motor and inverter operate as a boost converter, the 800V battery can be charged using an existing 400V charger. As a result of this increased availability, on-board boost charging is becoming more common. When an internal permanent magnet synchronous machine (IPMSM) is used as the boost inductor, the shape of the three-phase current changes because the current ripple varies with the rotor angle due to the magnetic saliency of the rotor. In addition, if the averages of the phase currents are not equal, torque can be produced. In this study, the complete IPMSM inductance model is utilized to obtain an analytical representation of the current ripple as a function of the switching duty and rotor angle. Based on this, the maximum charging current is estimated and the maximum charging power is also derived as a function of the rotor angle. It also determines the optimal rotor angle that minimizes the current ripple. This study also addresses phase current equalization to avoid torque generation. To this end, a compensation method is proposed to obtain an accurate average current in the double-sampling method, which samples the top and valley. The derived formulas are verified via simulations and experiments.